Tissue factor messenger RNA levels in leukocytes compared with tissue factor antigens in plasma from patients in hypercoagulable state caused by various diseases - Sase, Tomohiro; Wada, Hideo; Kamikura, Yuko; Kaneko, Toshihiro; Abe, Yasunori; Nishioka, Junji; Nobori, Tsutomu; Shiku, Hiroshi (Thrombosis and Haemostasis, 2004)
We compared the levels of tissue factor (TF) mRNA in leukocytes with plasma TF antigens of patients in hypercoagulable state caused by various diseases. Flow cytometric analysis showed absence of TF antigen expression on neutrophils and monocytes in healthy subjects but strong expression in both cell types of patients with infections. TF mRNA levels in leukocytes were low in healthy subjects but they were significantly elevated in patients with underlying diseases of disseminated intravascular coagulation (DIC), especially in acute myeloid leukaemia (AML) and infections. TF mRNA levels in leukocytes were significantly high in patients with all diseases except those with thrombosis, and plasma TF antigen levels were significantly high in all diseases. TF mRNA in leukocytes and plasma TF antigen levels were significantly high in patients with overt-DIC, and TF mRNA/antigen ratio was significantly high in patients with overt-DIC. In patients with solid cancers, TF mRNA and TF mRNA/antigen ratio were significantly higher in patients with metastases than those without. TF mRNA levels in leukocytes and plasma levels of TF antigen did not correlate in normal subjects and all patients, but they tended to be correlated in patients with AML, infections or overt-DIC. Our analysis suggests that TF expression in leukocytes plays an important role in various diseases but the expression level does not always correlate with plasma levels of TF antigen.
Keywords: Tissue factor; disseminated intravascular coagulation; infection; cancer; hypercoagulability